Introduction to Manuscripts “Umdat Al Jawahir of Sheikh Abdul Latif” and its place in exegetical literature - Abdun Nasir; Muhammad Asad; Muhammad Usama; Muhammad Farhan Ur Rehman (Correspondence Author); Abdur Rahman; Dr Mufti Maqsood ur Rehman (Al-Qanṭara, 2024)
This article contains an introduction to the manuscripts and its place in the exegetical literature. It consists of two parts; the first part is an introduction to the manuscript. The name of the manuscript is “Umdat Al Jawahir Wa Durar Yani Muqaddamat Al Quran Wa Rawabit Al Suwar”. And this name is written by the author himself on the first page of the manuscript. The author of this manuscript is Sheikh Abdul Latif. The author has indicated it in five places of his manuscript. Only one copy of this manuscript was with the scholar’s father Sheikh Saad Ud Din, Mufti Jamia Haleemia Darra Pezu Lakki Marwat. And there is no other copy of it. The exact date of the beginning and end of this manuscript cannot be determined. But it is traced that he wrote this manuscript in the year  during the vacations of Ramadan and Shaban. The second part of this article deals with the place of manuscript in exegetical literature. This manuscript is written in Arabic language. But there are few poems in Urdu and Persian and the style of the manuscript is in accordance with the rules of exegesis, in which the author uses verses and hadiths to make his point more authentic. The author distinguished himself from other mufassireern in some aspects of the manuscript while some of the aspects of his manuscript are in line with the traditional manuscripts. All the discussions in the manuscript are coherent. In addition, the author has also used the terms of Ilme Balaghat, while following the rules of sarf wa nahwa in the expressions.